Factors Related With Administration Of Colostrum For Newborns In Pmb Dince Safrina Of Pekanbaru City - ., Jasmi; Susilawati, Elly; Octafia, Mia (JURNAL IBU DAN ANAK, 2020)
Abstract Complete breastfeeding is strongly recommended by nutritionists around theworld as none of the formula can replace the baby's immune protection providedby colostrum produced during the first few days after birth. It is so beneficial forthe development of the baby. In addition, it is the first immunization received bythe baby since it contains high anti-infective substances up to 17 times more thanmature milk. The coverage of exclusive breastfeeding in Riau in 2016 was39.7%, still low compared to the 2016 strategic plan target of 42%. This studyaimed to determine the factors associated with the administration of colostrum tonewborns. This descriptive analytic research used a cross sectional designconducted at PMB Dince Safrina of Pekanbaru City from September 2017 toJune 2018. The sample size was 42 selected using accidental sampling. Dataanalysis used Chi Square. The results indicated that there was a relationship offamily support (p = 0.02), socio-cultural (0.03), and education (p = 0.02) tocolostrum administration. It is recommended to the midwife to always provideinformation to pregnant women about the importance of colostrum for the babyand motivate the mother to give colostrum to newborn at the time of delivery.